Construction of possible integrated predictive index based on EGFR and ANXA3 polymorphisms for chemotherapy response in fluoropyrimidine-treated Japanese gastric cancer patients using a bioinformatic method. Issue 1 (December 2015) - Takahashi, Hiro; Kaniwa, Nahoko; Saito, Yoshiro; Sai, Kimie; Hamaguchi, Tetsuya; Shirao, Kuniaki; Shimada, Yasuhiro; Matsumura, Yasuhiro; Ohtsu, Atsushi; Yoshino, Takayuki; Doi, Toshihiko; Takahashi, Anna; et al.
Abstract Background Variability in drug response between individual patients is a serious concern in medicine. To identify single-nucleotide polymorphisms (SNPs) related to drug response variability, many genome-wide association studies have been conducted. Methods We previously applied a knowledge-based bioinformatic approach to a pharmacogenomics study in which 119 fluoropyrimidine-treated gastric cancer patients were genotyped at 109, 365 SNPs using the Illumina Human-1 BeadChip. We identified the SNP rs2293347 in the human epidermal growth factor receptor (EGFR ) gene as a novel genetic factor related to chemotherapeutic response. In the present study, we reanalyzed these hypothesis-free genomic data using extended knowledge. Results We identified rs2867461 in annexin A3 (ANXA3 ) gene as another candidate. Using logistic regression, we confirmed that the performance of the rs2867461 + rs2293347 model was superior to those of the single factor models. Furthermore, we propose a novel integrated predictive index (iEA) based on these two polymorphisms inEGFR andANXA3 . Thep value for iEA was 1.47 × 10−8 by Fisher's exact test. Recent studies showed that the mutations inEGFR is associated with high expression of dihydropyrimidine dehydrogenase, which is an inactivating and rate-limiting enzyme for fluoropyrimidine, and suggested that the combination of chemotherapy with fluoropyrimidine and EGFR-targeting agents is effective against EGFR-overexpressing gastric tumors, whileANXA3 overexpression confers resistance to tyrosine kinase inhibitors targeting theEGFR pathway. Conclusions These results suggest that the iEA index or a combination of polymorphisms inEGFR andANXA3 may serve as predictive factors of drug response, and therefore could be useful for optimal selection of chemotherapy regimens.